Dose-finding study of Leuplin depot for prevention of premature luteinizing hormone surge during controlled ovarian stimulation: a pilot study in intrauterine insemination treatment - Heng-Ju Chen; Yu-Hung Lin; Mei-Zen Huang; Kok-Min Seow; Lee-Wen Huang; Bih-Chwen Hsieh; Chii-Ruey Tzeng; Jiann-Loung Hwang (Elsevier, 2016)
Objective: The standard dose of depot gonadotropin releasing hormone agonist (GnRHa) may be too much to prevent premature luteinizing hormone (LH) surge in controlled ovarian stimulation (COS). The purpose of this study was to find out the minimal effective dose of Leuplin depot to prevent premature LH surge in patients undergoing intrauterine insemination (IUI). Materials and Methods: From January 2006 to December 2007, unexplained infertile patients who were going to undergo IUI were recruited into the study. They were assigned sequentially to one of the following treatment groups. The first 50 patients received the 1/3-dose of Leuplin depot in the midluteal phase of the cycle preceding COS. If no premature LH surge occurred in the 50 patients, the study was continued with 1/4-dose of Leuplin depot in the subsequent 50 patients. Similarly, if no premature LH surge occurred with 1/4 dose, the study was continued with 1/5-dose of Leuplin depot in the following 50 patients. Ovarian stimulation was started with human menopausal gonadotropin (hMG) at 112.5 IU/d after downregulation, then IUI was performed 36 hours after human chorionic gonadotropin (hCG) injection. Results: Premature LH surge was effectively prevented with 1/3-dose and 1/4-dose of Leuplin depot. Premature LH surge occurred in three of the 50 patients (6%) in the 1/5-dose group. The patients in the 1/4-dose group received a significantly lower amount of hMG and fewer days of COS, compared with the 1/3-dose group. Conclusion: The 1/4 dose of Leuplin depot is the minimal effective dose to prevent premature LH surge. Further trial is worthwhile to compare the reducing dose Leuplin depot and daily low-dose leuprolide in in vitro fertilization (IVF) programs.